The Relationship Between Psychological Impact And Resilience And Social Support In School-Age Children After The Flood In The Taman Kintamani-Bekasi - Elfira Sri Futriani; Mustikasari Mustikasari; Achmad Setya Roswendi (Jurnal Ners, 2025)
Flood disasters have substantial psychosocial impacts on school-aged children, including depression, anxiety, and post-traumatic stress disorder (PTSD). Resilience and social support are critical protective factors that facilitate psychological recovery in this vulnerable group. This study aimed to examine the relationship between psychological impacts (depression, anxiety, PTSD), resilience, and social support among children affected by flooding.: A quantitative analytical study with a cross-sectional design was conducted on 60 children aged 6–12 years in Taman Kintamani Housing, Bekasi, using a total sampling technique. Data were collected using validated instruments: the Center for Epidemiological Studies Depression Scale for Children (CES-DC), the Chinese version of the State Anxiety Scale for Children (CSAS-C), and the PTSD Checklist. Analyses included univariate, bivariate (Chi-square), and multivariate (multiple logistic regression) tests.Most respondents were aged 10–12 years (73.3%) and male (53.3%). Significant associations were found between depression, anxiety, and PTSD with resilience (p = 0.018; p = 0.030; p = 0.013) and social support (p = 0.023; p = 0.036; p = 0.022). Children without depression were 4.48 times more likely to demonstrate high resilience (p = 0.032). Those with mild anxiety were nearly six times more likely to show high resilience compared to those with moderate/severe anxiety (p = 0.014). Similarly, children with mild PTSD were 5.25 times more likely to report high resilience (p = 0.015). Although not statistically significant, children aged 10–12 years tended to have higher resilience (OR = 3.07, p = 0.061), suggesting clinical relevance. Higher levels of depression, anxiety, and PTSD were associated with lower resilience and reduced social support among school-aged children after flooding. These findings highlight the importance of community-based psychosocial interventions aimed at strengthening coping strategies, enhancing social support, and empowering families to promote resilience and accelerate recovery in disaster-affected children.